Artificial General Intelligence: Advantages in English Language Learning - Yulian Purnama; Sherly Gaspersz (Yayasan Adra Karima Hubbi, 2024)
Learning English has become a major focus in this modern era, where cross-cultural communication is increasingly important. However, the language learning process is often challenging for many individuals, especially those who do not have adequate access or resources. The advent of Artificial General Intelligence promises significant advances in language learning approaches, with the potential to increase the accessibility, speed and effectiveness of learning. This research aims to explore the potential benefits of Artificial General Intelligence in English language learning, especially in the context of accessibility, speed and effectiveness of learning. The research method uses a qualitative approach involving a comprehensive literature study on the latest developments in the use of Artificial General Intelligence in language learning. The research results show that Artificial General Intelligence has great potential to improve English language learning. Apart from that, there are also many benefits to be gained from using Artificial General Intelligence in English language learning. The conclusions in this research confirm that the use of Artificial General Intelligence in English language learning offers significant potential to increase the accessibility, speed and effectiveness of learning. However, challenges related to ethics, privacy and data security also need to be seriously considered in the development and implementation of this technology. With a careful and integrated approach, Artificial General Intelligence can be a valuable tool in supporting inclusive and effective English language learning for all individuals. The limitation of this research is that this research only conducted research at the educational unit level, specifically in English language learning.